An empirical study on debt-equity ratio norms of the construction, property and hotel industries - Han, Bernard Cheung Yong (2013)
This report presents the findings of an empirical study of capital structure norms which was conducted on the construction, property and hotel industries in Singapore. The study hopes to determine if a capital structure norm exists in each of the industry.